2019
DOI: 10.1063/1.5091825
|View full text |Cite
|
Sign up to set email alerts
|

Energy distribution functions for ions from pulsed EUV-induced plasmas in low pressure N2-diluted H2 gas

Abstract: Energy distribution functions for ions from pulsed EUV-induced plasmas in low pressure N2-diluted H2 gas. Applied Physics Letters, 114(13), [133502].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Earlier investigations, using isolated pulses, showed that trace amounts of N 2 might indeed affect the plasma composition and chemistry but do not change the ion energy distribution function (IEDF) of the hydrogen ions significantly. 60 This was confirmed recently on an LPP testrig for regular 50-kHz multipulse mode of operation. No measurable difference in IEDF was observed for an addition of 10 −2 Pa of N 2 level in 5 to 10 Pa H 2 , as shown in Fig.…”
Section: Gas Puritysupporting
confidence: 55%
See 1 more Smart Citation
“…Earlier investigations, using isolated pulses, showed that trace amounts of N 2 might indeed affect the plasma composition and chemistry but do not change the ion energy distribution function (IEDF) of the hydrogen ions significantly. 60 This was confirmed recently on an LPP testrig for regular 50-kHz multipulse mode of operation. No measurable difference in IEDF was observed for an addition of 10 −2 Pa of N 2 level in 5 to 10 Pa H 2 , as shown in Fig.…”
Section: Gas Puritysupporting
confidence: 55%
“…The change in plasma composition might also change the plasma characteristics, as these heavier ions would diffuse out more slowly and would thus show more build-up over pulses. Earlier investigations, using isolated pulses, showed that trace amounts of N2 might indeed affect the plasma composition and chemistry, but do not change the IEDF of the hydrogen ions significantly 59 . This was confirmed recently on a LPP testrig for regular 50 kHz multi-pulse mode of operation.…”
Section: Gas Puritymentioning
confidence: 97%
“…Of main importance in the governing plasma dynamics are the (photo-and electron-impact) ionization cross sections, which impact the maximum plasma density, the ion mass of the specific gas, which impacts the rate of plasma expansion and decay and the possibility to excite specific molecular and/or atomic energy levels. Very recently, EUV-induced plasmas in N 2 -diluted H 2 gas have been studied [63]. From that study, it was concluded that the addition of even a small amount of N 2 (in the order of 0.1%) to H 2 resulted in a significant alteration of the ionic balance of the system and a rich chemistry producing NH-containing ions.…”
mentioning
confidence: 99%
“…However, the addition of small amounts of other gases can have an important influence on the composition of the EUV-induced plasma and it might significantly alter plasma chemistry and plasma physical processes, and hence representing real scanner conditions more accurately [62]. Although the first explorative study on N 2 -dilution of EUV-induced plasmas in H 2 has recently been published [63], there remains a strong demand from industry to understand the effect of other gases/vapors (e.g., H 2 O, O 2 , and N 2 ) on the whole model of EUV-induced plasma dynamics.…”
mentioning
confidence: 99%
“…Over the past decade, EUV-induced plasmas have been diagnosed extensively 1 , not only experimentally by monitoring dynamics of electrons [2][3][4][5][6] and ions [7][8][9] , but also by means of numerical simulations 10,11 . The interaction of those plasmas with contamination has been recently pinpointed as key by van de Kerkhof et al 12 .…”
Section: Introductionmentioning
confidence: 99%